2000
DOI: 10.1046/j.1365-2427.2000.00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of a lake outlet community to light and nutrient manipulation: effects on periphyton and invertebrate biomass and composition

Abstract: 1. Experimental channels were installed at the outlet of a small Canadian Shield lake to study the role of light and nutrients on the regulation of periphyton and invertebrate biomass and taxonomic composition. Light (93% reduction) and nutrients (four‐fold increase of ambient total phosphorus (TP) concentration) were manipulated in a factorial design experiment. 
2. Periphyton chlorophyll a (Chl a), measured four times during the 12‐week experiment, increased due to higher irradiance but was unaffected by pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 63 publications
(85 reference statements)
4
33
1
Order By: Relevance
“…It is worth noting that different species in grassland and afforested streams contributed to the predominance of larger species in this period, with the presence of some large diatoms in grasslands and cyanobacteria in afforested streams, each of which has different tolerance to stream conditions. This is similar to the results of Bourassa and Cattaneo (2000), who found higher proportion of cyanobacteria in shaded channels. The greatest proportion of sensitive and larger algae in the high water period suggests a higher availability of resources in this period (Larson and Passy 2012).…”
Section: Potential Mechanisms Explaining Patternssupporting
confidence: 92%
“…It is worth noting that different species in grassland and afforested streams contributed to the predominance of larger species in this period, with the presence of some large diatoms in grasslands and cyanobacteria in afforested streams, each of which has different tolerance to stream conditions. This is similar to the results of Bourassa and Cattaneo (2000), who found higher proportion of cyanobacteria in shaded channels. The greatest proportion of sensitive and larger algae in the high water period suggests a higher availability of resources in this period (Larson and Passy 2012).…”
Section: Potential Mechanisms Explaining Patternssupporting
confidence: 92%
“…Direct rates of sunlight in the water body (Tuji, 2000) and greater nutrient loading via allochthonous in water body both caused by the low proportion of riparian forest may favor the high algal development (Bourassa and Cattaneo, 2000). This possibly explains the more significant epiphyton in the impacted Palm swamps with low riparian vegetation cover, which is located in areas under agricultural and urban impacts, with greater nutrient loading.…”
Section: Discussionmentioning
confidence: 99%
“…We can predict that anthropogenic impacts change environmental characteristics, thus urban Palm swamps and in agriculture areas are related to various environment changes such as deforestation and higher allochthonous input of nutrients. Several studies have demonstrated that an increase in nutrients, in particular, increased productivity and periphytic chlorophyll (Dodds et al, 1997;Bourassa and Cattaneo, 2000), are therefore due to the density of periphytic algae of such environments.…”
Section: Introductionmentioning
confidence: 99%
“…Bourassa and Cattaneo 2000;James et al 2000;Rosemond et al 2000;Liboriussen et al 2005;Hillebrand 2008). We regard the structure of periphyton, developed in the macrophyte beds of the selected lakes, as the overall result of the interacting factors at their natural sites.…”
Section: Article In Pressmentioning
confidence: 99%